Stingray epidermal microbiomes are species-specific with local adaptations - Kerr, Emma N.; Papudeshi, Bhavya; Haggerty, Miranda; Wild, Natasha; Goodman, Asha Z.; Lima, Lais F. O.; Hesse, Ryan D.; Skye, Amber; Mallawaarachchi, Vijini; Johri, Shaili; Parker, Sophia; Dinsdale, Elizabeth A. (Frontiers in Microbiology, 2023)
Marine host-associated microbiomes are affected by a combination of species-specific (e.g., host ancestry, genotype) and habitat-specific features (e.g., environmental physiochemistry and microbial biogeography). The stingray epidermis provides a gradient of characteristics from high dermal denticles coverage with low mucus to reduce dermal denticles and high levels of mucus. Here we investigate the effects of host phylogeny and habitat by comparing the epidermal microbiomes of Myliobatis californica (bat rays) with a mucus rich epidermis, and Urobatis halleri (round rays) with a mucus reduced epidermis from two locations, Los Angeles and San Diego, California (a 150 km distance). We found that host microbiomes are species-specific and distinct from the water column, however composition of M. californica microbiomes showed more variability between individuals compared to U. halleri. The variability in the microbiome of M. californica caused the microbial taxa to be similar across locations, while U. halleri microbiomes were distinct across locations. Despite taxonomic differences, Shannon diversity is the same across the two locations in U. halleri microbiomes suggesting the taxonomic composition are locally adapted, but diversity is maintained by the host. Myliobatis californica and U. halleri microbiomes maintain functional similarity across Los Angeles and San Diego and each ray showed several unique functional genes. Myliobatis californica has a greater relative abundance of RNA Polymerase III-like genes in the microbiome than U. halleri, suggesting specific adaptations to a heavy mucus environment. Construction of Metagenome Assembled Genomes (MAGs) identified novel microbial species within Rhodobacteraceae, Moraxellaceae, Caulobacteraceae, Alcanivoracaceae and Gammaproteobacteria. All MAGs had a high abundance of active RNA processing genes, heavy metal, and antibiotic resistant genes, suggesting the stingray mucus supports high microbial growth rates, which may drive high levels of competition within the microbiomes increasing the antimicrobial properties of the microbes.